A configurational investigation of smartphone use disorder among adolescents in three educational levels. (April 2020) - Gao, Qiufeng; Jia, Ge; Fu, En; Olufadi, Yunusa; Huang, Yanlin
Highlights: Used ecological system theory to investigate adolescent smartphone use disorder. fsQCA is a rising person-centered approach for researching human behaviors. Smartphone use disorder became more severe as educational level went up. The core conditions for smartphone use disorder differed across educational levels. Abstract: Introduction: Smartphone use disorder in youth was associated with severe physical, psychological, and financial problems. Based on the ecological system theory of child development, this study examined a wide range of psychosocial characteristics in elementary-, middle-, and high-school adolescents with high scores on smartphone use disorder. Methodology: Existing research, which mainly adopted regression-based analytical techniques, found that gender, self-control, sensation seeking, loneliness, anxiety, perceived parent-adolescent relationship, and perceived parental monitoring are associated with smartphone use disorder. To complement traditional variable-centered approaches, the current study adopted a person-centered approach, fuzzy-set Qualitative Comparative Analysis (fsQCA) procedures, to examine adolescents with smartphone use disorder. Results: The fsQCA procedure revealed four, nine, and thirteen distinct configurations that contributed to smartphone use disorder in adolescents for elementary school students, middle school students, and high school students respectively. A comparison across the three educational levels revealed four differences and two similarities. The results suggest that different groups of adolescents might be at risk for smartphone use disorder across the three educational levels. Conclusions: The fsQCA procedures generated solutions with satisfactory coverage and consistency. This demonstrates the promising value of fsQCA for researching smartphone use disorder and other behavior problems in adolescents. The results suggest that educators and mental health practitioners should consider educational level when helping adolescents with smartphone use disorder.